Morphological Structure And Word Function Between The Arabic Linguistic Heritage And Modern Structural Linguistics - Hosni, Amina (El Omda in Linguistics and Discourse Analysis, 2023)
Abstract : The word in arabic grammar is comosed of phonimic units with a discriminarory value that plays its important role in charching the semantics and meanings. The triple division of Arabic words, which is composed of linguisti sounds with a distinctive function, is considered as one of the most important issues raised by Arabic linguists, which we find their correspondances in modern linguistic works difference in the method and way of studing, especiallyv in what Martini and Troubechkoy presented, the pioneers of the structural functional school